Analisis Yuridis terhadap Kewenangan Penamaan Jalan di Kota Mojokerto - Muhammad Muhammad; Bahrul Amiq; M. Yustino Aribawa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is based on the ambiguity of street naming norms in statutory regulations, this causes the legality of street naming in the Mojokerto city government area to be questioned.Based on this description, the author formulates the problem formulation as follows: (1) What is the authority of the Mojokerto City Government in naming roads? (2) What is the legality of naming roads belonging to the Mojokerto city government?.This research uses a normative juridical research type with a statutory approach, a historical approach and a conceptual approach using primary legal materials and secondary legal materials.The research results from this thesis show that the Mojokerto City Government does not have direct authority to name roads in its area. There is a lack of normative legal regulations in regulating transitional conditions in the naming of landforms, especially roads. The legality of naming roads belonging to the Mojokerto city government can be questioned due to the absence of statutory norms that order local governments to form legal products related to street naming.